Evaluation of glucose challenge test using cut off values 130mg/dl and 140 mg/dl for gestational diabetes mellitus screening - Basnet, Tulasa; Pradhan, Neelam; Koirala, Poonam; Bista, Kesang D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Gestational Diabetes Mellitus (GDM) is associated with several adverse maternal and perinatal outcomes. Thus, screening for early detection of GDM and its treatment is important. Methods: This was hospital based descriptive study done over one year in department of Obstetrics and Gynecology, TUTH, Nepal. Six hundred ninety-seven women fulfilling the inclusion criteria were enrolled at 18-22 weeks of gestation. High risk factors were assessed and GCT was performed in women with risk factors during enrollment. Diagnostic OGTT was performed in women who screened positive (GCT ≥130mg/dl). Screen negative high-risk women were re-screened at 24-28 weeks. In women without known risk factors, GCT was performed at 24-28 weeks and OGTT was performed when screen positive. The diagnosis of GDM was made according to Carpenter and Coustan criteria. Results: Out of 697 enrolled women, 12 were excluded for various reasons and 685 women were analyzed. Women having risk of GDM were 28.9%. The prevalence of GDM was 2.92% and 2.48% with GCT cut off 130 mg/dl and 140 mg/dl respectively. Lowering the threshold to 130 mg/dl identified three extra cases (p=0.010). The prevalence among high risk group was 8.58% and 7.07% with the cut off value 130 mg/dl and 140 mg/dl respectively with three extra cases detected on taking cut off value 130 mg/dl (p=0.014). Among low risk women the prevalence of GDM was same i.e. 0.61% with both the cut off values. Conclusions: Lowering threshold of GCT to 130 mg/dl could identify significant percentage of extra cases of GDM especially in high risk women.